(3eONdc Edi (BWindows version 3.1 (3hHQGeLg GdedMbI HGYJeGO GddZI GdYQHjI (B/s - (3NGdO CHh GdaJhM aVGdIs ((3GdbGgQI (B:s (3OGQ GdcJH GdYdejI,s, 1994)
(3eGPG JYQa Yf hjfOhR(B.s
Keywords: (3eGjcQhShaJ hjfOhR (B((3eda MGShH(B)s; (3fXe GdJTZjd (B((3MGSHGJ EdcJQhfjI(B)s